Governance of urban transitions: towards sustainable resource efficient urban infrastructures. (11th December 2017) - Swilling, Mark; Hajer, Maarten
Abstract: The transition to sustainable resource efficient cities calls for new governance arrangements. The awareness that the doubling of the global urban population will result in unsustainable levels of demand for natural resources requires changes in the existing socio-technical systems. Domestic material consumption could go up from 40 billion tons in 2010, to 89 billion tons by 2050. While there are a number of socio-technical alternatives that could result in significant improvements in the resource efficiency of urban systems in developed and developing countries (specifically bus-rapid transit, district energy systems and green buildings), we need to rethink the urban governance arrangements to get to this alternative pathway. We note modes of urban governance have changed over the past century as economic and urban development paradigms have shifted at the national and global levels. This time round we identify cities as leading actors in the transition to more sustainable modes of production and consumption as articulated in the Sustainable Development Goals. This has resulted in a surge of urban experimentation across all world regions, both North and South. Building on this empirically observable trend we suggest this can also be seen as a building block of a new urban governance paradigm. An 'entrepreneurial urban governance' is proposed that envisages an active and goal-setting role for the state, but in ways that allows broader coalitions of urban 'agents of change' to emerge. This entrepreneurial urban governance fosters and promotes experimentation rather than suppressing the myriad of such initiatives across the globe, and connects to global city networks for systemic learning between cities. Experimentation needs to result in a contextually appropriate balance between economic, social, technological and sustainable development.